Agere Contra: An "Ignatian Option" for Engagement with American Society and Culture - Benjamin T. Peters (Journal of Moral Theology, 2017)
I have broken my article into three parts. First, I look at some of the more recent discussions surrounding the idea that the Americanist proposition is no longer viable. Next, I suggest an alternative approach to social engagement that is rooted in Ignatian spirituality, one that is neither a wholesale withdrawal from nor blanket embrace of American life. Finally, I highlight some of figures who seem to embody this “Ignatian option,” in particular Dorothy Day and Pope Francis.